Redesign of the coal gate on a 20 ton/hour chain grate boiler at pt sopanusa - Suhariyanto; Rusdiyana, Liza; Dika Andini Suryandari; Dimitra Meidina Kusnadi; Hafizh Naufal Atho’ulloh (Faculty of Vocational Studies - Research Center, DRPM ITS, 2025)
A chain grate boiler is a type of boiler with a moving grate system to transport solid fuel through the furnace. The coal gate regulates the distribution flow of coal from the hopper to the furnace. In the 20 tons/hour capacity chain grate boiler at PT Sopanusa, the existing coal gate experienced mechanical failure due to damage to components in the roller chain, shaft, and bearings, so that it could not operate as a coal distribution regulator. To overcome this problem, it is necessary to redesign the coal gate on the 20 tons/hour capacity boiler chain grate hopper at PT Sopanusa. The main components, such as the chain, sprocket, worm gear, shaft, bearing, and pin on the coal gate, need to be redesigned to avoid mechanical failure of the coal gate. After redesigning the main components of the coal gate, a coal gate design that is compatible with the boiler chain grate construction will be obtained. The results of the coal gate redesign are as follows: a lifting chain with Chain Grade 80 type, 4 mm diameter, and a sprocket diameter of 320.92 mm; a worm gear with a ratio of 30:1 using hardened steel for the worm and phosphor bronze for the gear; a shaft with S45C material, 60 mm diameter; bearings using single row deep groove ball bearings, unit number ASB Bearing UCP 212; and pins made of SAE 1045 material with dimensions of 60x20x12 mm to support the manual coal gate mechanism on the 20 tons/hour capacity boiler chain grate at PT Sopanusa.